A New Method for Endoscopic Sampling of Submucosal Tissue in the Gastrointestinal Tract: A Comparison of the Biopsy Forceps and a New Drill Instrument. (December 2016) - Walther, Charles; Jeremiasen, Martin; Rissler, Pehr; Johansson, Jan L. M.; Larsson, Marie S.; Walther, Bruno S. C. S.
Background . Sampling of submucosal lesions in the gastrointestinal tract through a flexible endoscope is a well-recognized clinical problem. One technique often used is endoscopic ultrasound-guided fine-needle aspiration, but it does not provide solid tissue biopsies with preserved architecture for histopathological evaluation. To obtain solid tissue biopsies from submucosal lesions, we have constructed a new endoscopic biopsy tool and compared it in a crossover study with the standard double cupped forceps. Methods . Ten patients with endoscopically verified submucosal lesions were sampled. The endoscopist selected the position for the biopsies and used the instrument selected by randomization. After a biopsy was harvested, the endoscopist chose the next site for a biopsy and again used the instrument picked by randomization. A total of 6 biopsies, 3 with the forceps and 3 with the drill instrument, were collected in every patient. Results . The drill instrument resulted in larger total size biopsies (mm 2 ; Mann-Whitney U test, P = .048) and larger submucosal part (%) of the biopsies (Mann-Whitney U test, P = .003) than the forceps. Two patients were observed because of chest pain and suspicion of bleeding in 24 hours. No therapeutic measures were necessary to be taken. Conclusion . The new drill instrument for flexible endoscopy can safely deliver submucosal tissue samples from submucosal lesions in the upper gastrointestinal tract.